Targeting the Intrinsically Disordered Structural Ensemble of α-Synuclein by Small Molecules as a Potential Therapeutic Strategy for Parkinson’s Disease - Toth, Gergely (2014)
The misfolding of intrinsically disordered proteins such asa-synuclein, tau and the Abpeptide has been associated withmany highly debilitating neurodegenerative syndromes including Parkinson’s and Alzheimer’s diseases. Therapeutictargeting of the monomeric state of such intrinsically disordered proteins by small molecules has, however, been a majorchallenge because of their heterogeneous conformational properties. We show here that a combination of computationaland experimental techniques has led to the identification of a drug-like phenyl-sulfonamide compound (ELN484228), thattargetsa-synuclein, a key protein in Parkinson’s disease. We found that this compound has substantial biological activity incellular models ofa-synuclein-mediated dysfunction, including rescue ofa-synuclein-induced disruption of vesicletrafficking and dopaminergic neuronal loss and neurite retraction most likely by reducing the amount ofa-synucleintargeted to sites of vesicle mobilization such as the synapse in neurons or the site of bead engulfment in microglial cells.These results indicate that targetinga-synuclein by small molecules represents a promising approach to the developmentof therapeutic treatments of Parkinson’s disease and related conditions.